2013
DOI: 10.1038/tp.2013.72
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated dynorphin opioid peptides mediate alcohol-induced learning and memory impairment

Abstract: The dynorphin opioid peptides control glutamate neurotransmission in the hippocampus. Alcohol-induced dysregulation of this circuit may lead to impairments in spatial learning and memory. This study examines whether changes in the hippocampal dynorphin and glutamate systems are related, and contribute to impairment of spatial learning and memory in a rat model of cognitive deficit associated with alcohol binge drinking. Hippocampal dynorphins (radioimmunoassay) and glutamate (in vivo microdialysis) were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 74 publications
1
24
0
Order By: Relevance
“…The DYN/KOR system has also been linked to EtOH‐related cognitive impairment. One study conducted in Wistar rats found that 6 days of forced binge‐like EtOH administration resulted in cognitive deficits (i.e., increased escape latency) in a water maze task and elevated DYN levels in the hippocampus (Kuzmin et al., ). Treatment with nor‐BNI (either systemic or in the dorsal CA3 region of the hippocampus) restored escape behavior in the EtOH‐exposed rats whereas systemic nor‐BNI did not enhance performance in control subjects (Kuzmin et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The DYN/KOR system has also been linked to EtOH‐related cognitive impairment. One study conducted in Wistar rats found that 6 days of forced binge‐like EtOH administration resulted in cognitive deficits (i.e., increased escape latency) in a water maze task and elevated DYN levels in the hippocampus (Kuzmin et al., ). Treatment with nor‐BNI (either systemic or in the dorsal CA3 region of the hippocampus) restored escape behavior in the EtOH‐exposed rats whereas systemic nor‐BNI did not enhance performance in control subjects (Kuzmin et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…One study conducted in Wistar rats found that 6 days of forced binge‐like EtOH administration resulted in cognitive deficits (i.e., increased escape latency) in a water maze task and elevated DYN levels in the hippocampus (Kuzmin et al., ). Treatment with nor‐BNI (either systemic or in the dorsal CA3 region of the hippocampus) restored escape behavior in the EtOH‐exposed rats whereas systemic nor‐BNI did not enhance performance in control subjects (Kuzmin et al., ). In accordance with these preclinical findings, a comparison of postmortem human brain tissue in alcoholic and control subjects revealed greater expression of prodynorphin and KOR mRNA in areas implicated in the cognitive control of addictive behavior—dorsolateral PFC, orbitofrontal cortex, and hippocampus (Bazov et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Dynorphin activates an inwardly rectifying potassium channel as well as voltage gated potassium channels (Wimpey & Chavkin 1991), including functioning to inhibit M current, a voltage-dependent potassium current, in CA1 neurons (Madamba et al 1999). Administration of the KOR antagonist norBNI directly into the HIPP reversed ethanol-induced changes in glutamate transmission (Kuzmin et al 2013). Bilkei-Gorzo et al showed that mice lacking dynorphin show increased partner recognition; in addition, when exposed to object or social recognition paradigms, mice showed increased Dynorphin-A immunoreactivity in the hippocampus, central amygdala, and basolateral amygdala (Bilkei-Gorzo et al 2014).…”
Section: Circuitrymentioning
confidence: 99%
“…It may also inhibit the release of glutamate, GABA (Hjelmstad and Fields, 2001 , 2003 ), and serotonin (5-HT) (Pinnock, 1992 ; Tao and Auerbach, 2005 ). In terms of behavior, various studies across different species have demonstrated effects of dynorphins on memory, learning, and cognitive functions (Colombo et al, 1992 ; Yakovleva et al, 2007 ; Kölsch et al, 2009 ; Tejeda et al, 2012 ; Kuzmin et al, 2013 ; Bilkei-Gorzo et al, 2014 ). Dynorphins may also contribute to aberrant habit formation in humans, as shown by their link to drug consumption and addiction (Everitt et al, 2001 ; Hyman and Malenka, 2001 ; Shippenberg et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%